The gut metabolome in a cohort of pregnant and lactating women from Antioquia-Colombia - Londoño-Osorio, Sara; Leon-Carreño, Lizeth; Cala, Mónica P.; Sierra-Zapata, Laura (Frontiers in Molecular Biosciences, 2024)
Nutrition during the perinatal period is an essential component of health and one that can severely impact the correct development of a human being and its overall condition, in all the subsequent stages of life. The availability of several compounds, mainly macronutrients and micronutrients, plays a key role in the balanced nutrition of both mother and baby and is a process with direct relation to the gut microbiome. Thus, we hereby refer to the set of small molecules derived from gut microbiome metabolism as the gut metabolome. These continuous processes occurring in the gut of a gestating or lactating mother related to microbial communities and nutrients, can be revealed by metabolomics. In this study, we explore for the first time the gut metabolome of pregnant and lactating women, from our region of Antioquia-Colombia, applying untargeted metabolomics by LC-QTOF-MS, and molecular networking. Regarding the gut metabolome composition of the cohort, we found, key metabolites that can be used as biomarkers of microbiome function, overall metabolic health, dietary intake, pharmacology, and lifestyle. In our cohort, pregnant women evidenced a significantly higher abundance of prostaglandins, alkaloids, corticosteroids, organosilicons, and natural toxins, while in lactating women, lipids stand out. Our results suggest that unveiling the metabolic phenotype of the gut microbiome of an individual, by untargeted metabolomics, allows a broad visualization of the chemical space present in this important niche and enables the recognition of influential indicators of the host’s health status and habits, especially of women during this significant perinatal period. This study constitutes the first evidence of the use of untargeted LC-QTOF-MS coupled with molecular networking analysis, of the gut microbiome in a Colombian cohort and establishes a methodology for finding relative abundances of key metabolites, with potential use in nutritional and physiological state assessments, for future personalized health and nutrition practices.